Active ageing in Europe: methods, policies, and institutions ; Austrian country report - Ney, Steven (2004)
Abstract: Contents: Introduction; 1 The Institutional Topography of the Ageing Issue in Austria; 1.1 Core and Peripheral Organisational Networks in Austrian Policy Domains; 1.2 Balanced and Imbalanced Policy Domains; 2 Visions and Divisions: the Austrian Policy Debate; 2.1 Marginal Insiders and Outsiders; 2.2 The Hidden Divide: Productive Ageing versus Senior Citizenship; 2.3 The Structure of the Austrian Active Ageing Debate(s); 3 The Austrian Policy Landscape; 3.1 Creating Capabilities; 3.2 Recognising Capabilities; 3.3 Exploiting Capabilities; 4 Conclusion: Barriers to and Opportunities for Active Ageing Policies in Austria